A Kajian Penerapan Konsep Sustainable Architecture Pada Bangunan Kantor Bappeda Kab. Hulu Sungai Tengah - Radhiyani, Khalishah; Rahman, Akbar; Febrita, Yuswinda (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
The increasing energy consumption and environmental degradation issues have prompted the need to apply sustainable architectural principles that are responsive to climatic conditions, particularly in humid tropical regions. This study aims to examine the application of Olgyay’s Bioclimatic Design concept in the Office Building of the Regional Development Planning Agency (Bappeda) of Hulu Sungai Tengah Regency through analyses of thermal comfort, natural lighting, as well as building layout and orientation. The method employed consists of a literature review and visual analysis of the existing building design. The findings indicate that the configuration of opposing openings enables effective cross ventilation as a passive cooling strategy, supported by the use of overhangs, canopies, and pyramid-shaped roofs to reduce solar heat gain. The proportionate design of window openings also maximizes natural lighting, thereby reducing the need for artificial illumination. Furthermore, the building orientation, which minimizes direct sunlight exposure, along with the presence of landscape elements and transitional spaces, enhances the building’s passive performance. Overall, the analysis suggests that the building design adheres to Olgyay’s bioclimatic principles in achieving thermal comfort, energy efficiency, and high indoor environmental quality. These findings are expected to serve as a reference for designing climate-adaptive government buildings in tropical regions.